Sur les effets macroéconomiques d’une politique de taxation directe au Québec - Salvas-Bronsard, Lise; Ouellet, Pierre-Yvon (L'Actualité économique, 1978)
The object of this paper is twofold: 1) to introduce the disaggregated legal tax rates into a macroeconometric model containing disaggregated marginal propensities to consume; 2) to simulate variations of tax rates in order to study the relative efficiency of individual tax rates for economic stabilization and to look at the stability of the model with respect to the progressivity of these tax rates.